해양저서동물의 정량적 자료에 대한 정도관리 현실과 개선안 - 최진우; 김종성; 송성준; 류종성; 권봉오; CHOI, JIN-WOO; KHIM, JONG SEONG; SONG, SUNG JOON; RYU, JONGSEONG; KWON, BONG-OH (Pada (Hanʼguk Haeyang Hakhoe), 2021)
Marine benthic organisms have been used as the indicators for the environment assessment and recently considered as a very important component in the biodiversity and ecosystem restoration. In Korean waters, the quantitative data on marine benthos was used as one of major components for the marine pollution assessment for 50 years since 1970s. The species identification which is an important factor for the quantitative biological data was mainly performed by the marine benthic ecologists. This leads to the deterioration of the data quality on marine benthos from the misidentication of major taxonomic groups due to the lack of taxonomic expertise in Korea. This taxonomic problem has not been solved until now and remains in most data from national research projects on the marine ecosystems in Korean waters. Here we introduce the quality assurance and control (QA/QC) system for the marine biological data in UK, that is, NMBAQC (Northeast Atlantic Marine Biological Analytic and Quality Control) Scheme which has been performed by private companies to solve similar species identification problems in UK. This scheme asks for all marine laboratories which want to participate to any national monitoring programs in UK to keep their identification potency at high level by the internal quality assurance systems and provides a series of taxonomic workshops and literature to increase their capability. They also performs the external quality control for the marine laboratories by performing the Ring Test using standard specimens on various faunal groups. In the case of Korea, there are few taxonomic expertise in two existing national institutions and so they can't solve the taxonomic problems in marine benthic fauna data. We would like to provide a few necessary suggestions to solve the taxonomic problems in Korean marine biological data in short-terms and long-terms: (1) the identification of all dominant species in marine biological data should be confirmed by taxonomic expertise, (2) all the national research programs should include taxonomic experts, and (3) establishing a private company, like the Korea marine organism identification association (KMOIA), which can perform the QA/QC system on the marine organisms and support all Korean marine laboratories by providing taxonomic literature and species identification workshops to enhance their potency. The last suggestion needs more efforts and time for the establishment of that taxonomic company by gathering the detailed contents and related opinions from diverse stakeholders in Korea. 해양저서동물은 해양의 환경오염에 대한 모니터링과 평가에 활용되었고, 최근에는 생물다양성과 생태계 복원의 관점에서 매우 중요한 요소로서 인식되고 있다. 한국에 있어서도 오염상태를 평가하는 환경영향평가에 주요 구성원으로 들어가 있어서 많은 연안역에서 저서동물군집에 대한 정량적 연구가 1970년대 중반 이후 50년간 수행이 되었다. 이런 연구의 종 동정에는 생태전문가가 일정기간 분류에 대한 교육을 받아서 수행해 온 것이며, 그 과정에서 저서동물의 동정을 소홀히 하였거나 잘못 동정하여 정보축적에 혼선이 있었으며, 분류전문가 부족으로 저서생물 시료를 종 수준까지 다루지 못한 것이 현실이었다. 해양생태계 기본조사와 같은 국가적인 연구조사에서도 저서동물에 대한 종 동정에 분류학 전문가의 참여가 적다는 것이 현실이고, 이로 인한 저서동물군집 자료에서 일부 분류군의 종 동정이 미흡하여 자료의 질적 저하를 초래한 면이 있었다. 영국에서는 해양생물의 정량적 자료 생성을 표준화하기 위해서 1990년대 국가해양생물분석질관리계획(National Marine Biological Analytical Quality Control, NMBAQC Scheme) 이라는 정도 관리체계를 만들었고, 국가 해양모니터링 프로그램에 참여하는 모든 기관에 해양생물 분석역량을 측정하고, 미흡하면 재교육과 훈련을 수행하고 있다. 하지만 국내에는 아직 이러한 해양생물을 조정할 수 있는 기관과 인력이 미흡한 실정이다. 국립해양생물자원관과 같은 공인기관이 존재하고 있어도 생태자료를 담당할 인력 부족으로 생태자료의 정도관리를 맡기에는 현실적으로 어렵다. 따라서 이에 대한 개선안으로서 단기적으로는 (1) 최소한 주요 우점종에 대한 종 동정을 분류전문가에게 확인을 받는 방안, (2) 가능하면 생물군별로 분류전문가를 연구조사에 참여시키는 방안이 필요하고, 장기적으로는 (3) 다양한 분류전문가를 포함하는 (가칭) '(재단법인) 해양생물 분류협회'를 설립하여 생물자료에 대한 정도관리와 전문가 양성과 훈련을 주관하는 방안 등을 제안하는 바이다. 향후 법인의 설립에 대한 구체적인 방안이나 법제적인 문제는 학회나 공청회를 통하여 보완하는 방안이 있겠다.